Homotaurine Induces Measurable Changes of Short Latency Afferent Inhibition in a Group of Mild Cognitive Impairment Individuals - Martorana, Alessandro; Di Lorenzo, Francesco; Manenti, Guglielmo; Semprini, Roberta; Koch, Giacomo (Frontiers in Aging Neuroscience, 2014)
Current treatment options for patients with Alzheimer's disease (AD) are limited at providing symptomatic relief, with no effects on the underlying pathophysiology. Recently, advances in the understanding of the AD pathogenesis highlighted the role of ABeta (Aβ) oligomers particularly interfering with mechanisms of cortical plasticity such as long-term potentiation (LTP) and long-term depression (LTD). These findings led to the development of potential antiamyloid therapies, and among them homotaurine, a glycosaminoglycan (GAG) mimetic designed to interfere with the actions of Aβ early in the cascade of amyloidogenic events, and by its γ-aminobutyric acid type (GABA) A receptor affinity. Recently, we showed that AD patients have impaired LTP-like cortical plasticity, as measured by standard theta burst stimulation (TBS) protocols applied over the primary motor cortex (M1). Furthermore, AD patients have a weakened Short Latency Afferent Inhibition (SLAI), a neurophysiological measure of central cholinergic transmission, which changes reflect the cholinergic dysfunction occurring in the pathology. Here we aimed at investigating whether homotaurine administration could modulate in vivo measured mechanisms of synaptic plasticity, namely LTP and LTD, and also SLAI in a group of mild cognitive impaired patients. We observed that homotaurine administration did not induce relevant changes of both LTP and LTD recordings, while induced changes of SLAI in our group of patients. We suggest that homotaurine effects are dependent on changes of cortical GABA transmission suggesting a potential role for this compound in ameliorating the cholinergic transmission by modulating the inhibitory cortical activity.